THE ROLE OF SOCIAL SUPPORT AND SOCIAL MEDIA USE IN SHAPING MOTHERS’ KNOWLEDGE OF STUNTING IN INDONESIA: A CROSS-SECTIONAL STUDY - Laili Perdani, Agni; Zahira, Alifvia Fitri; Srinatania, Dewi (DPW PPNI Provinsi Jawa Barat, 2025)
Introduction: Stunting is a persistent global public health issue and a key target of the Sustainable Development Goals (SDGs) 2030. Indonesia has the third highest prevalence of stunting among Southeast Asian countries. Maternal knowledge plays a critical role in the prevention and management of stunting during early childhood. Purpose: This study aimed to examine the relationship between social support, social media use, and maternal knowledge regarding stunting. Methods: A quantitative, cross-sectional study was conducted at a Community Health Center in an urban area of Indonesia between May and June 2022. A total of 250 mothers with children under five years of age participated. Data were collected using structured questionnaires, including demographic characteristics, a maternal stunting knowledge scale, the Multidimensional Scale of Perceived Social Support, and a scale assessing perceived internet use. Data were analyzed using linear regression. Results: The mean maternal age was 29.8 years (SD ± 6.92), and the mean age of children was 25.90 months (SD ± 17.15). Most participants reported high social support (60.4%), had a senior high school education (60.8%), were multiparous (55.6%), and were unemployed (81.2%). The average score for social media usability was 24.65 (SD ± 3.33). A majority of mothers (89%) demonstrated good knowledge of stunting. Maternal education contributed 4.5% to the variance in stunting knowledge. Conclusion: Higher maternal education was significantly associated with greater knowledge of stunting, possibly due to better access to accurate health information. Enhancing maternal education and information access may support national efforts to reduce stunting prevalence.